THE EFFECTIVENESS OF NEEM LEAF ETHANOL EXTRACT ON THE IN VITRO OF RHIPICHEPALUS SANGUINEUS - Merdana, I Made; Hapsari, Ida Ayu Pasti; Muslih, Fuady (Buletin Veteriner Udayana, 2020)
The Neem leaves were very potential to developed as an anti-ectoparasite drug in pets. The purpose of this research was to determine the effectiveness of ethanol extract of Neem leaves (Azadirachta indica, A. Juss) against Rhipicephalus sanguineus dog by in vitro. Using a completely randomized design, 250 ticks were randomly divided into 5 groups with five repetitions. A gentle spray treatment of neem leaves extract, sequentially; P0 as negative control with Aquadest, P1 as positive control with 0.5% deltamethrin, P2 with 2.5% Neem leaves extract, P3 with 5% Neem leaves extract, P4 with 10% Neem leaves extract, Each group consists of 12 ticks that placed in petri dish with a cotton pad that has been sprayed with each solvent, then treated again by spraying it gently and equal. The results of the research showed that the ethanol extract of neem leaves proved to be very significant (P <0.01) against the mortality of R. sanguineus by in vitro. This research, solvent with 10% of neem leaves extract was most effective to exterminate R. sanguineus ticks with 100% mortality.